Neoadjuvant Immunotherapy for MSI-H/dMMR Locally Advanced Colorectal Cancer: New Strategies and Unveiled Opportunities - Zhang, Xuan; Wu, Tao; Cai, Xinyi; Dong, Jianhua; Xia, Cuifeng; Zhou, Yongchun; Ding, Rong; Yang, Renfang; Tan, Jing; Zhang, Lijuan; Zhang, Ya; Wang, Yuqin; et al. (Frontiers in Immunology, 2022)
Patients with locally advanced colorectal cancer (LACRC) have a high risk of recurrence and metastasis, although neoadjuvant therapy may provide some benefit. However, patients with high microsatellite instability/deficient mismatch repair (MSI-H/dMMR) LACRC receive little benefit from neoadjuvant chemoradiotherapy (nCRT) or neoadjuvant chemotherapy (nCT). The 2015 KEYNOTE-016 trial identified MSI-H/dMMR as a biomarker indicative of immunotherapy efficacy, and pointed to the potential use of immune checkpoint inhibitors (ICIs). In 2017, the FDA approved two ICIs (pembrolizumab and nivolumab) for treatment of MSI-H/dMMR metastatic CRC (mCRC). In 2018, the CheckMate-142 trial demonstrated successful treatment of mCRC based on “double immunity” provided by nivolumab with ipilimumab, a regimen that may become a standard first-line treatment for MSI-H mCRC. In 2018, the FDA approved nivolumab alone or with ipilimumab for patients who progressed to MSI-H/dMMR mCRC after standard chemotherapy. The FDA then approved pembrolizumab alone as a first-line treatment for patients with MSI-H/dMMR CRC that was unresectable or metastatic. There is now interest in using these drugs in neoadjuvant immunotherapy (nIT) for patients with MSI-H/dMMR non-mCRC. In 2020, the NICHE trial marked the start of using nIT for CRC. This novel treatment of MSI-H/dMMR LACRC may change the approaches used for neoadjuvant therapy of other cancers. Our review of immunotherapy for CRC covers diagnosis and treatment, clinical prognostic characteristics, the mechanism of nIT, analysis of completed prospective and retrospective studies, and ongoing clinical trials, and the clinical practice of using nIT for MSI-H/dMMR LACRC. Our team also proposes a new organ-preservation strategy for patients with MSI-H/dMMR low LARC.